EFFECT OF COOPERATIVE LEARNING TYPE INVESTIGATION GROUP (GI) MODEL WITH EXPERIMENTAL OF COGNITIVE LEARNING OUTCOMES ENVIRONMENTAL SCIENCE EDUCATION STUDY PROGRAM BIOLOGY - Sri Purwati (PROSIDING SEMINAR KIMIA, 2015)
This study aims to determine the effect of learning model Group Investigation (GI) with the experimental method on cognitive learning outcomes of students. The study population was all students of biology education second semester, Academic Year 2014/2015. The sample in this study was determined by cluster random sampling technique consists of two classes namely class A (treatment) using Group Investigation learning model (GI) and class B (control). Data collection techniques using test techniques to get the data the cognitive learning. This type of research is a quasi experimental study. Design research in this study using a pretest-posttest design. Data analysis techniques in this study using statistical analysis techniques with separated variance t test. Cognitive learning outcomes the average value of class A (treatment) 78.09 70.95 while the control class. Results of t-test showed significant value 0:03 <0:05 so that we can conclude the learning model Group Investigation (GI) effect on the cognitive learning Environmental Science Biology Education Program.